1995
DOI: 10.1002/fld.1650200803
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation and optimal shape for viscous flow by a fictitious domain method

Abstract: SUMMARYIn this article we discuss the fictitious domain solution of the Navier-Stokes equations modelling unsteady incompressible viscous flow. The method is based on a Lagrange multiplier treatment of the boundary conditions to be satisfied and is particularly well suited to the treatment of no-slip boundary conditions. This approach allows the use of structured meshes and fast specialized solvers for problems on complicated geometries. Another interesting feature of the fictitious domain approach is that it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 11 publications
0
59
0
Order By: Relevance
“…where the matrix block D is the same one as in (18). The matrix block S for the Lagrange multipliers has the form…”
Section: Dirichlet Boundary Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…where the matrix block D is the same one as in (18). The matrix block S for the Lagrange multipliers has the form…”
Section: Dirichlet Boundary Conditionsmentioning
confidence: 99%
“…Another possibility is to add some constraints to the extended problem. This can be done using boundary Lagrange multipliers [18,19,44] or using distributed Lagrange multipliers [16,17,27,44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glowinski et al 19 also demonstrated the ef®ciency of this type of method for predicting the three-dimensional¯uid¯ow around a sphere imbedded in a rectangular domain and for solving an optimal shape problem involving two-dimensional Navier±Stokes¯ows. 20 The objective of this paper is to introduce a new three-dimensional ®ctitious domain method for the solution of the Navier±Stokes equations in enclosures containing internal parts which may be moving.…”
Section: Introductionmentioning
confidence: 99%
“…We refer to the text books [2,3,4] for a description of this classical approach to shape optimization. In [5] (see also [9]) a new approach based on a combination of the fictitious domain approach and optimal control was proposed in the case when the state is given by a homogeneous Dirichlet boundary value problem. The original optimal shape design problem was formally rewritten as a new one which uses as state problem again a homogeneous Dirichlet problem but posed on a a fixed domain and with the control entering only in the right hand side.…”
Section: Introductionmentioning
confidence: 99%